Redescription of 13 holotypes of Rheocricotopus Brundin, 1956 (Diptera: Chironomidae) from the Sino–Indian Region - Fu, Yue; Huang, Jingli; Liu, Wenbin; Fang, Xiangliang; Wang, Xinhua (Zootaxa, 2016)
Thirteen holotypes of the orthoclad genus Rheocricotopus from Sino–Indian Region: R. (Psilocricotopus) hidakadeeus Sasa & Suzuki, R. (P.) isigadeeus Sasa & Suzuki, R. (P.) kurocedeus Sasa, R. (P.) tokarakeleus Sasa & Suzuki, R. (P.) tobatervicesimus Kikuchi & Sasa, R. (Rheocricotopus) inaquereus Sasa, Kitami & Suzuki, R. (R.) inaxeyeus Sasa, Kitami & Suzuki, R. (R.) shoufukusecundus Sasa, R. (R.) tamahumeralis Sasa, R. (R.) tatequintus Sasa, R. (R.) tedorisecundus Sasa, R. (R.) togapeniculus Sasa & Okazawa and R. (R.) yakulemeus Sasa & Suzuki are re-examined and illustrated, Some additional descriptions, corrections and a key of these thirteen holotypes are given.